Revising the Project of Modernity: Hermeneutics - Šaulauskas, Marius Povilas (Problemos, 1998)
The article is intended t o argue the fundamental modernity of Habermasian, Gadamerian and, to a considerable extent, Rortyan philosophical projects in spite of their “self-limiting” and thereby “transcending” modem metanarrative characteristics. An indispensable presupposition of the Cartesian epistemology could be interpreted capitalizing on Habermasian concept of performative individuality and communicative action. As with the hermeneutical situation of Rousseau’s confession, Cartesian epistemological Ego always posits itself in terms of simultaneously naming and reflecting action that is always performed in the face of (real or simulated) second-person audience. The self-accountable realization of being epistemologically alone goes hand-to-hand with the necessary existence of the (one or many) Other-You, be it the Almighty, society or History. Therefore the (Cartesian) epistemological performative stand is indispensable in attributing an independent variable status both to modem subjectivity (as articulated by Descartes and Schleiermacher) or “post-modern” intersubjectivity. The latter is advocated, their quarrel notwithstanding, by Gadamer and Habermas, as well as by various other approaches, intended to break through the boundaries of modem philosophy, e.g. by the hermeneutical pragmaticism of Richard Rorty.